Effect of Cutaneous Leishmaniasis Treatment on Serum Adenosine/Deoxyadenosine Deaminase Activities - Culha, Gulnaz; Berkoz, Mehmet; Yalin, Serap; Gulkan, Burcu (Asian Journal of Chemistry, 2011)
Adenosine deaminase is an enzyme present in a great number of plants and animals, found from simple intervebrates to human beings. Adenosine deaminase and deoxyadenosine deaminase activities increase substantially during mitogenic and antigenic responses of lymphocytes and conversely lymphocytes blastogenesis. Various diseases characterized by the alteration of cell-mediated immunity can be effected by the serum activity of adenosine deaminase. Cutaneous leishmania is an intracellular parasite that targets and multiplies within phagocytic cells of the innate immune system such as the macrophage, dendritic cell and neutrophil. In this study, we investigated the role of treatment on adenosine deaminase and deoxyadenosine deaminase activities in the cutaneous leishmaniasis patients. For this aim, 25 treated cutaneous leishmaniasis patients, 19 untreated patients and 25 healthy control subjects were enrolled in this study. The clinical diagnosis was parasitologically confirmed Giemsa stain and by culture NNN medium. Adenosine deaminase and deoxyadenosine deaminase activities were measured spectrophotometrically by the method of Giusti. Serum adenosine deaminase and deoxyadenosine deaminase activities were higher in cutaneous leishmaniasis patients than the controls and also, adenosine deaminase and deoxyadenosine deaminase activities decreased in treated patients as compare with non-treated cutaneous leishmaniasis patients. According to these results, it is suggested that evaluation of adenosine deaminase activity in serum of patients with cutaneous leishmaniasis could be considered a useful monitoring tool for their infection status. Therefore, adenosine deaminase can be a predictive and sensitive parameter of leishmaniasis treatment.